Dietary habit of chronic periodontitis patients based on Balanced Nutrition Guidelines from the Ministry of Health of the Republic of Indonesia - Kono, Ghinda Nevithya; Hendiani, Ina; Komara, Ira (Padjadjaran Journal of Dentistry, 2021)
Introduction: Prevalence of the periodontal disease in Indonesia is 73.1%; one of them is periodontitis. Periodontitis is an inflammation of the tooth-supporting tissue caused by specific microorganisms or a specific group of microorganisms, destroying the periodontal ligament and alveolar bone with increased of clinical attachment loss. Chronic periodontitis patients generally have a poor dietary habit. This study was aimed to describe the dietary habit of chronic periodontitis patients at Universitas Padjadjaran Dental Hospital. Methods: The research method used was descriptive survey research. This study's population was diagnosed with chronic periodontitis based on medical records at the Clinics of Periodontics Specialist Program of Universitas Padjadjaran Dental Hospital. The research sample was taken by purposive sampling. The number of samples in this study was taken through the Lemeshow formula A total of 43 research respondents who met the inclusion and exclusion criteria. Respondents were asked to fill out a questionnaire regarding their diet. Results: This study showed that the study respondents were averagely consumed three portions of staple food, two portions of side dishes, one portion of vegetables, and one portion of fruits. Conclusion: Dietary habit of chronic periodontitis patients are mostly not following the Balanced Nutrition Guidelines from the Ministry of Health of the Republic of Indonesia regarding the types of staple foods, side dishes, vegetables, and fruits.